Whole-genome assemblies of 16 Burkholderia pseudomallei isolates from rivers in Laos - Liechti, N; Zimmermann, RE; Zopfi, J; Robinson, MT; Pierret, A; Ribolzi, O; Rattanavong, S; Davong, V; Newton, PN; Wittwer, M; Dance, DAB (American Society for Microbiology, 2021)
We report 16 Burkholderia pseudomallei genomes, including 5 new multilocus sequence types, isolated from rivers in Laos. The environmental bacterium B. pseudomallei causes melioidosis, a serious infectious disease in tropical and subtropical regions. The isolates are geographically clustered in one clade from around Vientiane, Laos, and one clade from further south.